Sanga Literature and Ethnography : சங்க இலக்கியமும் இனவரைவியலும் - K. Satish (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2021)
The Tamil Classical Sangam Literature is often treated as a source to trace the social, cultural, and civilization of ancient Tamil. Though there have been many endeavors have been completed, there was still much to be explored and studies. New studies offer new insights into acknowledging ancient society in detail. Still, the new arrival of extravagations extends the spectrum to another level. One that is worthy of studying in the social structure of ancient society. It has been well established that the social structure of Sangam society was classified based on the local landscape and it has been designed using the concept of Tinai and its classifications. An ethnic group living in a specific eco-zone with unique culture can be called Tinai culture. ait is delineated in Sangam classics. This can be attributed to empirical sources like hero-stones, coins, and others. By way of analyzing these sources, we can identify the different layers in Sangam society. This article focuses on varied ritual systems that are described in Sangam Literature. சங்ககாலச் சமூக அமைப்பு நிலபாகுபாட்டின் அடிப்படையில் வரையறுக்கப் பட்டுள்ளது. அதனைத் ‘திணைச்சமூகம்’ என்னும் சொல்லாடல் மூலம் குறிக்கிறோம். ஒருகுறிப்பிட்ட நிலவரையறைக்கு உட்பட்ட பகுதியில் வாழும் மக்களைத் திணைச்சமூகம் என்றும் அம்மக்களின் வழக்கங்களைத் திணைப்பண்பாடு என்றும் அழைக்கிறோம். இதற்கு இலக்கியத் தரவே அடிப்படையாக அமைகிறது. இவை தவிர பிறசான்றுகளும் உள்ளன. நடுகற்கள், காசுகள் போன்ற சான்றுகள் இலக்கியத்திலும் கிடைக்கின்றன. இன்று வரை கிடைத்த தரவுகளின் அடிப்படையில் திணைச்சமூகத்தின் பண்பாடுகளை ஓரளவு மீட்டுருவாக்கலாம். சங்க கால இலக்கியத்தின் வழி சமூகத்தை ஆராய்கிறபோது அதனுள் பன்மை அடுக்கு அமைப்பு (multi-layer system) இருப்பதை உணரமுடிகிறது. இந்தக் கட்டுரை சங்க இலக்கியத்தில் காணப்படும் சடங்கின் பன்மை அடுக்கு நிலையினை முன்வைகிறது.